Eating disorders, body image, emotion, and self-esteem in adults: A systematic review - Marzieh Abdoli; Elisabeth Schiechtl; Marco Scotto Rosato; Paolo Cotrufo; Katharina Hüfner (Bern Open Publishing, 2024)
Introduction & Purpose Eating disorders, body image, self-esteem, and emotional issues affect psychological and physical health and often co-occur. Disturbances in body image can trigger and worsen disordered eating behaviours. Emotions and self-esteem are influential factors in both eating disorders and body image issues, impacting their severity and manifestation. The interconnection of eating disorders, body image, emotions, and self-esteem has mostly been studied in adolescents, while there has been less research on the adult population. This systematic review seeks to synthesise existing literature on the comorbidity and coexistence of eating disorders, body image disturbance, emotion, and self-esteem in the adult population. Methods Following the PRISMA guidelines, a systematic search was conducted in scientific databases (PubMed, Scopus, and Web of Science) for articles published between 2010 and 2024 (Figure 1). The selected studies focused on the connections between eating disorders, body image, emotion, and self-esteem in adult populations. Six studies were selected from an initial collection of 1,117 articles, with most female participants representing different racial backgrounds. The study participants were required to be over 18 years old and use standard tools to measure the variables, and only original research with significant results was included. Results Individuals with eating disorders showed higher levels of body dissatisfaction, which was linked with lower self-esteem and emotional dysregulation. Women with bulimia nervosa displayed higher emotion-oriented coping strategies compared to controls, resulting in low self-esteem (Wölfges et al., 2011). Obese patients with binge-eating disorders (BED) had more negative attitudes towards obesity compared to obese individuals without BED, correlating with higher levels of depression and disordered eating behaviours (Barnes et al., 2014). The African American participants reported lower weight bias than white participants (Lewer et al., 2015). Furthermore, body image disturbances were a consistent theme, particularly their role in worsening eating disorders, with findings showing that body dissatisfaction indirectly influenced disordered eating behaviours through its effects on self-esteem and depression (Brechan & Kvalem, 2015). The findings revealed that women are more vulnerable to the negative impacts of body image dissatisfaction and emotional dysregulation on eating disorders (Barnes et al., 2014; Brechan & Kvalem, 2015). Additionally, the impact of weight bias and dissociative experiences during sexual activities, which were linked to binge eating and sexual dissatisfaction, was highlighted (Castellini et al., 2017). Discussion The findings emphasise the connections between self-esteem, body image, emotion, and eating disorders. Professional interventions for eating disorders should consider improving self-esteem and providing adaptive emotion techniques to enhance body image perception. The importance of self-compassion in improving body image and managing eating disorders was also noted (Kelly et al., 2014). More research on adult populations in non-Western countries is needed. Conclusion This review emphasises the relationships between eating disorders, body image, self-esteem, and emotion in adults. Moreover, the combination of strategies that improve emotional regulation, self-esteem, and body image perception within clinical interventions could lead to more practical management of eating disorders in adults. Future research should explore these variables across different cultures with varied research strategies. References Barnes, R. D., Ivezaj, V., & Grilo, C. M. (2014). An examination of weight bias among treatment-seeking obese patients with and without binge eating disorder. General Hospital Psychiatry, 36(2), 177-180. https://doi.org/10.1016/j.genhosppsych.2013.10.011 Brechan, I., & Kvalem, I. L. (2015). Relationship between body dissatisfaction and disordered eating: Mediating role of self-esteem and depression. Eating Behaviors, 17, 49-58. https://doi.org/10.1016/j.eatbeh.2014.12.008 Castellini, G., Lo Sauro, C., Ricca, V., & Rellini, A. H. (2017). Body esteem as a common factor of a tendency toward binge eating and sexual dissatisfaction among women: The role of dissociation and stress response during sex. The Journal of Sexual Medicine, 14(8), 1036-1045. https://doi.org/10.1016/j.jsxm.2017.06.001 Kelly, A. C., Vimalakanthan, K., & Miller, K. E. (2014). Self-compassion moderates the relationship between body mass index and both eating disorder pathology and body image flexibility. Body Image, 11(4), 446-453. https://doi.org/10.1016/j.bodyim.2014.07.005 Lewer, M., Nasrawi, N., Schroeder, D., & Vocks, S. (2015). Body image disturbance in binge eating disorder: A comparison of obese patients with and without binge eating disorder regarding the cognitive, behavioral and perceptual component of body image. Eating and Weight Disorders - Studies on Anorexia, Bulimia and Obesity, 21, 115-125. https://doi.org/10.1007/s40519-015-0200-5 Wölfges, R., Legenbauer, T., & Hiller, W. (2011). Überprüfung des aktuellen Stressbewältigungsverhaltens bulimischer Frauen in einer sozialen Interaktion [Examination of the current stress management behaviour of bulimic women in a social interaction]. Verhaltenstherapie, 21(1), 23-29. https://doi.org/10.1159/000324255